Papel das elites no desenvolvimento político e econômico do município de Uberaba (MG) - 1910 a 1960 - Wagner, Roberta Afonso Vinhal (2006)
The present Master dissertation analyzes the elites paper in the economic and political development of Uberaba city and the consequences in the production of the geographic space. This research occupy the period that extends of 1910 to 1960. We work with boarding theoretician and methodological of historical Geography and we seek to understand the relations of economic, social, cultural and politics production in Uberaba, constructing an analysis of the elites in their diversity and analyzing the power of these groups in different dimensions. The knowledge of the historic aspects of some social groups helps to explain the geographic transformations occurred in that space, and hinders the construction of models that do not correspond with the reality. In this perspective, we think that is essential to understand the (re)construction of the hegemonic power of these elites, as well as their values and strategies. In this research, in Uberaba (1910-1960), while maintenance instrument of the power in the economic relations, we evidenced that the political elaborated social nets that had formed a resistant society to the process of capitalist development.